Empirical study of software process improvement in Malaysian small and medium enterprises: The human aspects. Issue 10 (16th April 2018) - Almomani, Malek Ahmad; Basri, Shuib; Gilal, Abdul Rehman
Abstract: Software Process Improvement (SPI) aims to achieve quality software products in software companies. Ignoring human factors can cause several types of damage in the software development process. Because, Software development is not a purely technical task, but rather it is a relationship between technical and human factors that interact with each other constantly. Currently, Small Medium Enterprises' (SMEs) software development companies in Malaysia still struggle to implement SPI successfully. Therefore, the main objective of this study is to investigate the empirical evidence based on the human factor perspective for helping Malaysian SMEs' software development companies to implement SPI strategies. A questionnaire‐based survey method was used for gathering information from 79 practitioners. The results indicate that 9 factors (employee awareness, leadership involvement, employee involvement, customer involvement, senior management support, staff experience, staff learning, staff skills, and client support) are considered important for implementing SPI in Malaysian SME software development companies. The involvement of both leadership and employees, and getting support from management are the most important human factors that should be considered during the design process of SPI strategies.